ANALISIS PRODUK PEMBIAYAAN MURABAHAH PADA BMT PERMATA (studi kasus pada BMT Permata Mojokerto Jawa Timur) - Ziyadatur Rosyada; Mohammad Habibi (STAI AN-NAJAH INDONESIA MANDIRI, 2021)
This research raises the theme of Murabahah financing products at BMT Permata Mojokerto, East java. This is motivated by the development of islamic financial Institutions which also indicated by the high number of BMT (Baitul Maal Wat Tamwil) BMT it self is a sharia financial institution that provides sharia financing services to businesses micro for its members the existence of BMT is strategic, especially to reach rural areas (agricultural sector and informal sector).This study aims to determine how the systematics of Murabahah financing Products at BMT Permata Mojokerto, East Java. This type of research is qualitative research. The research data were obtained thourgh observation, interviews and documentation methods found in the field. Often used for buying and selling transactions of course because it has many advantages and disadvantages, as for the advantages, namely the Margin of Murabahah profit is fixed (certainty) (2) in financing products there are advantages that are given, such as easy checking of financing through mobile gems, other bank transfers can be entered directly to the BMT savings account and can be directly checked via the BMT mobile, without making direct deposit to the BMT office Keywords: BMT, Financing, Murabahah References Ahmad Ifham Sholihin, Pedoman Umum Lembaga Keuangan Syariah (Jakarta: PT Gramedia Pustaka Utama, 2010), 457 Azhar Muttaqin (2012) Model Pembiayaan BMT dan Perannya dalam pembinaan kesejahteraan usaha kecil menengah (UKM) Departemen Pendidikan Nasional, Kamus Besar Bahasa Indonesia Pusat Bahasa, (Jakarta PT Gramedia Pustaka Utama 2008) Dody Setiawan (2019). Laporan PraktikKerja Lapangan (PKL) Pada BMT Ta’awun Finance (BMT Tawfin) bidang Pemasaran, UNEJ Kasmir, Manajemen Perbankan (Jakarta: PT Raja Grafindo Persada, 2001), 92 Nur Rianto, Lembaga Keuangan Syariah (Bandung: CV Pustaka Setia, 2012), 149 Metode Penelitian Kuantitatif,Kualitatif dan R&D, hlm,304 Muhammad Syafi’i Antonio, Bank Syariah dari Teori ke Praktik (Jakarta: Gema Insani Press, 2001), 160. Muhammad, Lembaga-Lembaga Keuangan Umat Kontemporer (Yogyakarta: UII Press), 260. Syafi’i Antonio, Bank Syari’ah dari Teori ke Praktek, 170. Wiroso, Jual Beli Murabahah (Yogyakarta: UII Press, 2005)